Effectiveness of Educational Intervention Based on the Extended Theory of Planned Behavior on Exclusive Breastfeeding - Farahnaz Yazdanpanah; Mostafa Nasirzadeh; Hassan Ahmadinia; Mahdi Abdolkarimi; Fatemeh Askari (Gonabad University of Medical Sciences, 2024)
Background: Breastfeeding is one of the most effective ways to ensure a child's health. This study investigated the effect of an extended theory of planned behavior (TPB) on exclusive breastfeeding (EBF). Methods: In this randomized educational trial, 132 pregnant women were divided into two intervention groups and one control group using a multi-stage random clustering method. The first intervention group received interventions based on the TPB. In the extended theory group, interventions to promote breastfeeding self-efficacy and social support for breastfeeding were also provided. In order to collect information, the constructs of the planned behavior questionnaire, Dennis's breastfeeding self-efficacy questionnaire and boateng's breastfeeding social support questionnaire were used, all of which have confirmed validity and reliability. Data were analyzed using the paired t-test, analysis of covariance, one-way analysis of variance, and chi-square and Bonferroni tests.  Results: All the constructs of the TPB in both groups improved after the intervention (P<0.05). The results also showed that although the breastfeeding self-efficacy score was improved in the extended group (0.009), the three groups did not show significant differences in this regard (P=0.241). Although the social support score improved in the extended group, this difference was not statistically significant (P=0.145). The analysis of variance revealed that the scores for intention and behavior had significant differences among the three groups (P=0.0001). However, the post hoc Bonferroni test showed no significant difference between the two intervention groups (P>0.05).  Conclusion: This study showed that the constructs of both the TPB and the extended TPB could effectively promote EBF behavior. It appears that combining the use of planned behavior theory constructs with social support structures and breastfeeding self-efficacy can be effective in promoting breastfeeding behavior.